Post-calving photo-census of the Rivière George caribou herd in July 1993 - Russell, J.; Couturier, S.; Sopuck, L.G.; Ovaska, K. (Rangifer, 1996)
A photographie census of the Rivière George caribou herd in Quebec and Labrador was conducted between 4-23 July 1993 during the post-calving period. The primary objective of the study was to obtain an accurate estimate of the current size of the herd to permit the monitoring of population trends and effective management of the herd. The census procedure consisted of (1) use of satellite and conventional radio-telemetry to locate and photograph post-calving aggregations during the period of optimal aggregation, (2) determination of the minimum population size by direct counts from photographs, and (3) estimation of the total population size using the Petersen Index method. This method allowed extrapolation of the data to caribou that were either not photographed or that were not aggregated at the time of the census. The minimum count indicates that the Rivière George caribou herd consisted of at least 358 460 adults (older than calves) at the time of the census. This count underestimates the total population size but is useful because it is virtually free of error. The total size of the Rivière George herd in July 1993 was estimated to be 540 040 adults within 90% confidence limits of + 12.8%. Comparisons with previous estimates indicate that the size of the herd continues to be large, but that its growth has probably ceased. This study demonstrates that a photographic survey of post-calving aggregations is an effective method to census the Rivière George herd and possibly other large migratory caribou herds that are monitored by telemetry.